Highly efficient visible light-induced photocatalytic degradation of methylene blue over InVO4/BiVO4composite photocatalyst - Umaporn Lamdab (2018)
© 2015, Springer Science+Business Media New York. A highly efficient and visible light responsive photocatalyst was developed by indium vanadate (InVO4)/bismuth vanadate (BiVO4) composite photocatalyst. The samples were characterized by X-ray diffraction (XRD), Brunauer–Emmett–Teller, scanning electron microscopy, transmission electron microscopy (TEM), UV–Vis diffuse reflectance spectra, XPS, zeta potential, and photoluminescence techniques. The XRD, TEM, and XPS results indicated the prepared sample was actually a two-phase composite: InVO4and BiVO4. Photocatalytic activities of all catalysts were evaluated for the degradation of methylene blue in aqueous solution under visible light irradiation. The highest activity was obtained in the InVO4/BiVO4composite using 0.8:0.2 mol ratio of InVO4:BiVO4. On the basis of the calculated energy band positions, the mechanism of enhanced photocatalytic activity was discussed.